2002
DOI: 10.1295/polymj.34.383
|View full text |Cite
|
Sign up to set email alerts
|

Microcalorimetric Study of Aqueous Solution of a Thermoresponsive Polymer, poly(N-vinylisobutyramide) (PNVIBA)

Abstract: ABSTRACT:A temperature-responsive synthetic vinyl polymer with hydrogen-bonding and hydrophobic side residues, poly(N-vinylisobutyramide) (PNVIBA), was studied for its calorimetric properties in aqueous solutions. The temperature-responsive behavior was dependent on the polymer concentration at lower range and also on the concentration of added sodium dodecyl sulfate (SDS) at higher range. Thermodynamic parameters and molecular weight dependence were discussed in comparison with the corresponding results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…Figure 8 shows T cp s vs. polymer molecular weights for well-defined PNIPAM samples with different end-groups. For hydrophilic endgroups such as amino, the polymers showed inverse molecular weight dependence of the T cp , in good agreement with previous studies [28][29][30][31][32]. However, the T cp was found to be directly dependent upon polymer molecular weight for hydrophobic end-groups.…”
Section: Thermoresponsivity Of Pnipams Before and After Click Reactionsupporting
confidence: 91%
See 2 more Smart Citations
“…Figure 8 shows T cp s vs. polymer molecular weights for well-defined PNIPAM samples with different end-groups. For hydrophilic endgroups such as amino, the polymers showed inverse molecular weight dependence of the T cp , in good agreement with previous studies [28][29][30][31][32]. However, the T cp was found to be directly dependent upon polymer molecular weight for hydrophobic end-groups.…”
Section: Thermoresponsivity Of Pnipams Before and After Click Reactionsupporting
confidence: 91%
“…The bisalkynelinked PNIPAM that was designed as no end-group effect reference gave the smallest molecular weight dependence among the three series studied here. As mentioned above, previous studies of PNIPAM and other thermoresponsive polymers have demonstrated the LCST to be independent [32][33][34]45], directly dependent [10,26], or inversely dependent [17,[27][28][29][30][31]46,47] upon polymer molecular weight. LCSTs are expected to be decreased with increasing molecular weight on the basis of the changes in the polymer-solvent interaction [48,49].…”
Section: Thermoresponsivity Of Pnipams Before and After Click Reactionmentioning
confidence: 78%
See 1 more Smart Citation
“…Inomata et al [32] as well as Kunugi et al [33] performed lightscattering experiments in order to extract information about the spinodal decomposition of the aqueous solution of PNIPAM.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding energy is ÀT c ÁS ¼ 3:62 Â 10 6 J mol À1 . The hydration entropy loss per monomer was measured for free PNIPAM chains in water and is $10 J K À1 mol À1 [17]. Thus, if chains were to behave as free chains, we would have $10 3 equivalent monomers per particle.…”
mentioning
confidence: 99%